The impact of the reflective teaching model on developing the skills of the university art education teacher (Journal of the College of Basic Education, 2022)
The research aimed to design a training unit to master the technical skills of the university teacher. To demonstrate the effectiveness of the unit, the university teacher does a practical application exercise using the reflective teaching method. The research sample consisted of (28) participants in a qualifying course for teaching methods from university graduates as a university teacher. They were subjected to a training program that lasted for two weeks, during which training practices were presented by the participants through the reflective teaching method. Statistical methods were used to process the results, including the t-test, Cooper's equation. The results showed that the experimental group outperformed the post-test. This is because of the training lectures presented that made it easier for the participants to master the skillful performance of the training practices using reflective teaching.